2021
DOI: 10.1002/vetr.199
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of abdominal ultrasound for detecting non‐perforated gastroduodenal ulcers in dogs

Abstract: Background Abdominal ultrasound is frequently used to detect non‐perforated gastroduodenal ulcers in dogs. Studies assessing the diagnostic utility of abdominal ultrasound for the detection of non‐perforated gastroduodenal ulcers have yielded mixed results. No studies to date have investigated the effects of patient bodyweight, breed, sex, age, ulcer aetiology (neoplastic or inflammatory) or location on the diagnostic accuracy of abdominal ultrasound. Methods Retrospective, multicentre study to evaluate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The limited number of cases presented herein may justify the absence of hepatobiliary diseases as being among the causes of the ulceration; hepatobiliary diseases are In the present study population, abdominal ultrasound findings regarding duodenal ulcers were not consistently reliable, with a 55% incidence of non-specific increased duodenal wall thickness in the affected patients. The latter was not entirely surprising, as several studies have reported a low sensitivity of abdominal ultrasound examination for the detection of nonperforated gastroduodenal ulcers in dogs (Fitzgerald et al, 2017;O'Kell et al, 2022;Weston et al, 2022). Conversely, as previously reported by Saravanan et al (2012), the endoscopic approach seemed to be the most accurate technique for the early diagnosis of duodenal mucosal ulcers, useful both in defining the extent of the lesion, and for selecting the appropriate treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The limited number of cases presented herein may justify the absence of hepatobiliary diseases as being among the causes of the ulceration; hepatobiliary diseases are In the present study population, abdominal ultrasound findings regarding duodenal ulcers were not consistently reliable, with a 55% incidence of non-specific increased duodenal wall thickness in the affected patients. The latter was not entirely surprising, as several studies have reported a low sensitivity of abdominal ultrasound examination for the detection of nonperforated gastroduodenal ulcers in dogs (Fitzgerald et al, 2017;O'Kell et al, 2022;Weston et al, 2022). Conversely, as previously reported by Saravanan et al (2012), the endoscopic approach seemed to be the most accurate technique for the early diagnosis of duodenal mucosal ulcers, useful both in defining the extent of the lesion, and for selecting the appropriate treatment.…”
Section: Discussionmentioning
confidence: 67%
“…In the present study population, abdominal ultrasound findings regarding duodenal ulcers were not consistently reliable, with a 55% incidence of non‐specific increased duodenal wall thickness in the affected patients. The latter was not entirely surprising, as several studies have reported a low sensitivity of abdominal ultrasound examination for the detection of non‐perforated gastroduodenal ulcers in dogs (Fitzgerald et al ., 2017; O'Kell et al ., 2022; Weston et al ., 2022). Conversely, as previously reported by Saravanan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, clinical signs, laboratory findings, and abdominal ultrasound findings were not consistently indicative of GDU. The latter is not totally surprising because studies have reported sensitivities of abdominal ultrasound examination for nonperforated GDU in dogs ranging from 30‐65% 15,18 . Because not all of the dogs in our study had ultrasound examination immediately before endoscopy, it is also possible that ulcers detected at endoscopy were not present at the time of the ultrasound examination.…”
Section: Discussionmentioning
confidence: 80%
“…The latter is not totally surprising because studies have reported sensitivities of abdominal ultrasound examination for nonperforated GDU in dogs ranging from 30-65%. 15,18 Because not all of the dogs in our study had ultrasound examination immediately before endoscopy, it is also possible that ulcers detected at endoscopy were not present at the time of the ultrasound examination. The exclusion of dogs receiving acid suppressant medication may have biased our study population toward dogs without clinical signs or laboratory abnormalities suggestive of GDU.…”
Section: Discussionmentioning
confidence: 99%